Change Management CM - Hala Soud Alrashidi; Majdi Anwar Quttainah (Journal of International Conference Proceedings (JICP), 2018)
This paper examines the management of change in organizations, individuals or institutions, and what each of them requireschanging whether it is in part of the company or in full. Change management is a comprehensive term that covers all types of processes that are carried out to prepare and support organizational change. This is a set of methodologies applied to resources, business processes, budget allocations and other operational aspects of the project. Change management in the context of project management often refers to the process of controlling change when working on a project. That is, the process of changes is formally introduced into the project scope and adopted as a change management system.